Theoretical and methodological principles of teaching geography in a specialized school (Pedagogy of Higher and Secondary Education, 2021)
The article studies the issue of theoretical and methodical basis of geography teaching in the profile school. Educational content's structure as analysed. The analyse and monitoring conclusions on pedagogical experiment to find out the level geography knowledge of high school students are being revealed.
Keywords: educational content's structure; profile geography teaching; elective courses; theoretical and methodical basis; pedagogical experiment